Ягорлицькі кургани на Лівобережжі Дністра (історія вивчення, картографія та топографія) - Сапожников, І.В.; Болтрик, Ю.В. (Археологія і давня історія України, 2018)
Статтю присвячено забутому, проте дуже важливому, скупченню курганів між невеликими степовими річками Мокрий Ягорлик та Сухий Ягорлик на лівобережжі Середнього Дністра. На підставі аналізу різнорідних джерел встановлюються назви курганів та окреслюється загальна топографічна ситуація розташування ланцюга насипів, зведених вздовж одного із стародавніх шляхів. Обґрунтовується думка, що кургани були зведені вздовж стародавнього шляху, що вів до гирла Дунаю на півдні, а північні гілки розходились в напрямку поселенських структур середньої течії Південного Бугу і Середнього Дніпра. The article is devoted to the kurgans which are located on the 45 km long cape, formed by the valleys of the Yagorlyk and Sukhyi Yagorlyk rivers, which merge at the left bank of the Dniester. These burial mounds were mentioned and even painted by J. A. Münz (1781), and then described and put on cards by A. K. Meyer and F. P. de Volan (1791). Topographers and archaeologists have noted up to 120 mounds reaching a height of 8—9 m in this local region. Most of them are stretched along the top of the watershed, some groups stand with two parallel lines, a number of chains of kurgans are oriented across the watershed. In general, they mark the site of the ancient trade route, along which it was possible to travel from the Dniester to the north to the forest-steppe; to the east to the Dnipro region and to the south-east to the Danube delta and the Black Sea.